Effects of replacing concentrates with cassava products on feed intake, digestibility, and rumen fermentation in Thai native cattle (Journal of Advanced Veterinary and Animal Research, 2026)
Objective: The study investigated the effect of replacing concentrate with dried cassava tops and fermented cassava pulp (CtFCp) on feed efficiency, nutrient intake, and rumen fermentation in Thai native cattle. Materials and Methods: A completely randomized design with three dietary treatments was conducted with female Thai native cattle, initially weighing approximately 97 kg. The dietary treatments consisted of 100% concentrate (Control), 67% concentrate mixed with 33% dried CtFCp-33, and 33% concentrate mixed with 67% dried CtFCp-67, all based on dry matter (DM). Results: DM intake and digestibility were lower (p < 0.05) in the CtFCp-67 treatment than in other treatments. In addition, crude protein digestibility increased (p < 0.001) in the CtFCp diets. At 4 h post-feeding, concentrations of acetate and propionate were significantly decreased in the CtFCp-67 treatment, while total volatile fatty acids and butyrate were also significantly decreased (p < 0.05). Estimated methane emissions were lower in CtFCp-67 than CtFCp-33 (p < 0.05). Conclusion: CtFCp can replace up to 33% of concentrate in Thai native cattle diets without affecting intake or digestibility. Further studies should assess the effects of lactating cows.J. Adv. Vet. Anim. Res., 12(4): 1159–1167, December 2025http://doi.org/10.5455/javar.2025.l977